Spinal CCL1/CCR8 regulates phosphorylation of GluA1-containing AMPA receptor in postoperative pain after tibial fracture and orthopedic surgery in mice. (May 2020) - Wang, Chunyan; Xu, Rubin; Wang, Xueling; Li, Qing; Li, Yize; Jiao, Yang; Zhao, Qi; Guo, Suqian; Su, Lin; Yu, Yang; Yu, Yonghao
Highlights: Tibia fracture generates mechanical and cold allodynia after orthopedic surgery. Fracture elevates spinal CCL1/CCR8 expression and AMPA receptor activity. Central CCL1/CCR8 inhibition alleviates fracture-induced postoperative pain and spinal phosphorylation of AMPA receptor. Spinal blockage of GluA1-containing AMPA receptor alleviates fracture-induced postoperative pain. GluA1-containing AMPA receptor antagonist reverses the CCL1-induced pain hypersensitivity. Abstract: Chronic postoperative pain might be a pivotal component hindering recovery and regains the function after bone fracture and orthopedic surgery. However, the underlying mechanisms remain largely unclear. AMPA receptor of excitatory synapses is considered due to its critical role in pathologic pain. Chemokine CCL1 related neuroinflammation plays a role in excitatory synaptic transmission and nociceptive transduction. This study examined whether spinal CCL1 is associated with fracture-associated postoperative pain via AMPA receptor. We herein discovered that the tibial fracture with orthopedic surgery initiated and maintained chronic postoperative pain along with spinal up-regulation of CCL1/CCR8 expression and phosphorylation of GluA1-containing AMPA receptor. Central CCL1/CCR8 inhibition impaired mechanical and cold allodynia, and phosphorylated GluA1-containing AMPA receptor in the spinal dorsal horn. Intrathecal injection of GluA1-containing AMPA receptor antagonist NASPM alleviated fracture-related postoperative pain. Also, exogenous CCL1 delivery facilitated acute pain behaviors and spinal phosphorylation of GluA1-containing AMPA receptor in naïve mice, reversing by co-application of NASPM. Our current results indicated that spinal CCL1/CCR8-mediated GluA1-containing AMPA receptor activation is vital in the pathogenesis of fracture associated postoperative pain in mice.